Bacterial Profile and Antibiotic Susceptibility Pattern of Urinary Tract Infection among Pregnant Women Attending Antenatal Care at a Tertiary Care Hospital in Southern Ethiopia - Ashenafi Tula; Abraham Mikru; Tsegaye Alemayehu; Beyene Dobo (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Urinary tract infection is one of the most common bacterial infections encountered in pregnant women with significant morbidity. This study aimed to determine the bacterial profile and its antimicrobial susceptibility pattern of urinary tract infection among pregnant women attending antenatal care (ANC) at a Hawassa University Comprehensive Specialized Hospital (HUCSH), Southern Ethiopia. Method. A cross-sectional study was conducted in which consecutive pregnant women enrolled in the study from March to June 2019. The structured questionnaire used to collect sociodemographic and clinical data in a face-to-face interview. Midstream urine was collected from pregnant women using sterile containers. Culture and sensitivity were performed using a standard operating procedure of the microbiology laboratory. Data entry and analysis were conducted using the statistical package for social sciences (SPSS) version 20. Descriptive and logistic regression was used to conduct the output of the data. The odds ratio at 95% confidence interval was considered as a statistically significant association with a p value <0.05. Result. The overall magnitude of urinary tract infection in this study was 7.8% (4.7–10.8%). Escherichia coli was found to be the most frequently isolated (47.8%), followed by Klebsiella pneumoniae (17.4%), Staphylococcus aureus (8.7%), Klebsiella ozaenae, Klebsiella rhinoscleromatis, Citrobacter spp., Salmonella group A, Staphylococcus saprophyticus, and Enterobacter cloacae each (4.3%). Gram-negative bacteria were sensitive to 78.3%, 91.3%, and 100% of ciprofloxacin, gentamicin, and nitrofurantoin, respectively. Gram-positive bacteria were sensitive to clindamycin (100%), gentamicin (100%), and nitrofurantoin (100%) and fully resistant to ceftriaxone (100%) and cefuroxime (100%). There is no statistically significant association (p < 0.05) between the risk factor of urinary tract infection and UTI. Conclusion. The overall prevalence of urinary tract infection among pregnant women attending antenatal care was 7.8%. Escherichia coli were the dominant isolate followed by Klebsiella pneumoniae. Gram-negative isolates are highly sensitive to ciprofloxacin, gentamicin, nitrofurantoin, and ceftriaxone and Gram-positive isolates to gentamicin, clindamycin, and nitrofurantoin. Most of the bacteria are resistant to cotrimoxazole and cefuroxime. There is no statistically significantly associated variable. Screening for the presence of urinary tract infection during pregnancy will improve the quality of antenatal care further reducing complication. The above antibiotics can be prescribed based on the side effect to pregnant women in case empirical treatment is mandatory in the study area.